2022
DOI: 10.3390/bios12090753
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Early Alzheimer’s Disease Diagnosis Using a Neural Network Hybrid Platform

Abstract: Early diagnosis of Alzheimer’s Disease (AD) is critical for disease prevention and cure. However, currently, techniques with the required high sensitivity and specificity are lacking. Recently, with the advances and increased accessibility of data analysis tools, such as machine learning, research efforts have increasingly focused on using these computational methods to solve this challenge. Here, we demonstrate a convolutional neural network (CNN)-based AD diagnosis approach using the surface-enhanced Raman s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, due to insufficient literature included, the AUC value could not be calculated, which is also worth further exploration. In the application of different diagnostic models, we found that there were differences in the sensitivity and specificity of different models, this study found that there are diagnostic models based on CNN ( 15 , 30 ), LDA ( 16 , 17 , 19 , 20 ), SVM ( 18 ), MLP ( 21 ) and ANN ( 22 ), and the AUC value of LDA used in more studies was 0.934, which was not much different from that of pooled AUC, which seemed to suggest that LDA was suitable for the diagnosis and recognition of Raman spectroscopy in AD. Due to the limited number of other types of diagnostic models, it is not possible to calculate the AUC of other types of diagnostic models.…”
Section: Discussionmentioning
confidence: 73%
“…However, due to insufficient literature included, the AUC value could not be calculated, which is also worth further exploration. In the application of different diagnostic models, we found that there were differences in the sensitivity and specificity of different models, this study found that there are diagnostic models based on CNN ( 15 , 30 ), LDA ( 16 , 17 , 19 , 20 ), SVM ( 18 ), MLP ( 21 ) and ANN ( 22 ), and the AUC value of LDA used in more studies was 0.934, which was not much different from that of pooled AUC, which seemed to suggest that LDA was suitable for the diagnosis and recognition of Raman spectroscopy in AD. Due to the limited number of other types of diagnostic models, it is not possible to calculate the AUC of other types of diagnostic models.…”
Section: Discussionmentioning
confidence: 73%
“…The authors employed the ADNI dataset for the experimental study and achieved 99.79% accuracy. X. Yu et al [20] introduced a new method for identifying AD. They applied CNN with surface-enhanced Raman Spectroscopy (SERS) fingerprints of human Cerebrospinal Fluid (CSF).…”
Section: A Analysis Of Admentioning
confidence: 99%
“…Structural MRI [6], [20], [26], [34], [35], [40] GARD Investigation 4: How does the strategic optimization of hyperparameters influence the convergence and generalization capabilities of DL models intended for ADidentifying biomarkers? PS: The optimization of hyperparameters is vital in the construction of DL models for the discovery of AD biomarkers.…”
Section: Figure 5 Ad Detection Using Various Technique Modelsmentioning
confidence: 99%
“…15 Xie group investigated the self-association and LODs of Aβ peptides in detail 16,17 and further demonstrated a convolutional neural network-based AD diagnosis approach using the SERS fingerprints of human cerebrospinal fluid (CSF). 18 Compared with conventional disease diagnosis methods such as ELISA, chromatography, and mass spectrometry, SERS technology has the advantages of high sensitivity and convenience of detection and analysis, which makes it highly promising in the early diagnosis of some intractable diseases such as AD. 15 High-performance substrate paves the way for the application of SERS technology.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al detected the AD markers Tau protein and Aβ42 peptide using three-dimensional (3D) gold nanowire arrays prepared by nanoimprinting as solid SERS substrates and obtained the limit of detections (LODs) of 10 –11 moles per liter (M) and 10 –9 M of the two biomarkers, respectively, corresponding to a SERS enhancement factor (EF) of 5.5 × 10 5 . Xie group investigated the self-association and LODs of Aβ peptides in detail , and further demonstrated a convolutional neural network-based AD diagnosis approach using the SERS fingerprints of human cerebrospinal fluid (CSF) . Compared with conventional disease diagnosis methods such as ELISA, chromatography, and mass spectrometry, SERS technology has the advantages of high sensitivity and convenience of detection and analysis, which makes it highly promising in the early diagnosis of some intractable diseases such as AD …”
Section: Introductionmentioning
confidence: 99%